Molecular species identification and spatio-temporal assessment of genetic diversity in the smooth hammerhead shark Sphyrna zygaena in South Africa - Kuguru, Gibbs (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.